2023
DOI: 10.1101/2023.03.15.532795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological signatures of temporal context in the bisection task

Abstract: Despite relatively accurate time judgment, subjective time is susceptible to various contexts, such as sample spacing and frequency. Several electroencephalographic (EEG) components have been linked to timing, including the contingent negative variation (CNV), offset P2, and late positive component of timing (LPCt). However, the specific role of these components in the contextual modulation of perceived time remains unclear. In this study, we conducted two temporal bisection experiments, where participants had… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…For the target offset signals, we observed that the offset P2 amplitude increased with duration, consistent with previous studies showing a positive association between P2 amplitude and stimulus duration (Baykan, Zhu, Zinchenko, et al, 2023;Kruijne et al, 2021;van Wassenhove & Lecoutre, 2015). This phenomenon indicates early perceptual processes rather than subsequent decisional stages (Kruijne et al, 2021).…”
Section: The Influence Of the Target Range During Encodingsupporting
confidence: 91%
See 3 more Smart Citations
“…For the target offset signals, we observed that the offset P2 amplitude increased with duration, consistent with previous studies showing a positive association between P2 amplitude and stimulus duration (Baykan, Zhu, Zinchenko, et al, 2023;Kruijne et al, 2021;van Wassenhove & Lecoutre, 2015). This phenomenon indicates early perceptual processes rather than subsequent decisional stages (Kruijne et al, 2021).…”
Section: The Influence Of the Target Range During Encodingsupporting
confidence: 91%
“…Previous research pointed out a relationship between CNV amplitude and response readiness, which in turn, influences response speed (Boehm et al, 2014). Similarly, in a recent study, we observed a more rapid CNV formation for the stimuli anticipated to end sooner (Baykan, Zhu, Zinchenko, et al, 2023). Our current investigation revealed a steeper CNV buildup and increased amplitude for durations during the BR session.…”
Section: The Influence Of the Target Range During Encodingsupporting
confidence: 90%
See 2 more Smart Citations
“…This prior is then integrated with the current duration (Bausenhart et al, 2014;Cicchini et al, 2012;Glasauer & Shi, 2021;Jazayeri & Shadlen, 2010;Shi, Church, et al, 2013;Shi & Burr, 2016), causing judgments to gravitate toward a mean duration. Varying the spacing or distribution of sample intervals can shift the temporal bisection point, a middle point of judgments between the given 'short' and 'long' standards, toward the ensemble mean (Baykan et al, 2023;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%